Measurement and Comparison of Pattern of Bone Destruction in Chronic Periodontitis Patients with and Without Smoking Habit: A Cross-Sectional Study - Anshika Suman; Shyamalendu Laskar; Parth Sharma; Anshu Nishchhal; Shambo Dey; Prasanta Majumder (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Smoking is a major risk factor for the development and advancement of periodontal disorders, which in turn cause the loss of periodontal attachment, deeper pockets, and the loss of tooth and alveolar bone. Aim: The purpose of this research is to use radiovisiography (RVG) radiographs in conjunction with transgingival probing to assess and quantify the pattern and degree of alveolar bone deterioration in individuals with chronic periodontitis (CP), whether or not they smoke. Materials and Methods: The research comprised 50 male volunteers with CP, 25 of whom were smokers and 25 of whom were not. Patients in Group A were those who were systemically healthy, had clinical attachment loss of ≥3 mm, were between the ages of 25 and 50, smoked 100 cigarettes or more throughout their lifetime, and were not smokers at the time of the interview. Group B was made up of non-smokers. Clinical data were documented, including clinical attachment loss (CAL), plaque index (PI), and probing pocket depth (PPD). RVG and transgingival probing were used to measure the amount and pattern of bone loss. Results: Compared to non-smokers, cigarette smokers had higher and statistically significant mean values for PI, PPD, and CAL. In the maxillary arch, cigarette smokers saw more bone loss than non-smokers. In cigarette smokers, the types of bone damage exhibited a more vertical pattern. Conclusion: In conclusion, it was shown that those who smoke have more bone loss than those who do not smoke. Since digital radiography has the ability to quantify bone change more precisely, transgingival probing in conjunction with RVG is a better way to evaluate bone loss.